Navigating a “New Normal” During the COVID-19 Pandemic: College Student Perspectives of the Shift to Remote Learning - Mollenkopf, Dawn; Gaskill, Martonia; Nelson, Rebecca; Diaz, Chandra (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2020)
The current COVID-19 pandemic has rapidly shifted institutions of higher education to remote learning environments, which has impacted student learning in unknown ways. The authors surveyed college students to determine how learning was impacted by the shift to remote learning during the COVID-19 pandemic, and to identify both the factors that created barriers and the factors that helped students succeed. Results indicate four primary factors — instructional design, instructor interactions, student autonomy and responsibility, and life/environmental factors — intersected to create the student learning environment. Implications for addressing barriers and increasing student success are discussed.